Pengaruh Perlakuan Filler Serat Kulit Buah Pinang Menggunakan Silane Coupling Agent terhadap Sifat Fisis dan Mekanis Papan Partikel - Delovita Ginting; Wulandari (Sistem Informasi, 2022)
This study aims to examine the effectiveness of the addition of Silane Coupling Agent on physical properties (density, moisture content, thickness expansion, and water absorption) and flexural strength in the manufacture of areca nut peel fiber particle board with urea formaldehyde adhesive. The betel nut peel fiber was alkalized using NaOH for 2 hours, then mashed using a grinding machine until it passed a 50 mesh sieve. The betel nut skin fibers that have passed the sieve are then treated with a solution of Silane Coupling Agent. The concentration variations of the Silane Coupling Agent solution were 0%, 2%, 4%, 6% and 8%. The betel nut peel fiber that has been synthesized with a silane coupling agent solution is then mixed with urea formaldehyde resin in a ratio of 30/70 in weight percent. The particleboard compaction process uses a Hydraulic Cold Press compacting machine with a pressure of 5 bar and a holding time of 120 minutes. The results of this study indicate that the silane coupling agent treatment increases the bond between the matrix and filler as shown in the SEM test on particle boards with 8% silane coupling agent treatment. The results of the particleboard test on density, percentage of moisture content, percentage of thickness development have met the standard of SNI 03-2105-2006. The results of the water absorption test have met the ASTM D 570 standard. The results of the flexural strength test on the SCA 6% variation SNI 03-2105-2006 decorative particle board type 8 and the SCA 8% variation have met the SNI standard 03-2105-2006 structural particle board type 10.5.